Q&A - Ask Doubts and Get Answers
Q

Use a suitable identity to get each of the following products. (x + 3) (x + 3)

Q : 1      Use a suitable identity to get each of the following products.

 

             (i) (x+3)(x+3)

Answers (1)
Views

(x + 3) X (x +3) = (x +3)^{2}
So, we use identity I for this which is 
                                                            (a+b)^{2} = a^{2} + 2ab + b^{2}
In  this  a=x and b = x 
                                    (x+3)^{2} = x^{2} + 2(x)(3)+ 3^{2}
                                                        =x^{2} + 6x+ 9            

Exams
Articles
Questions